Chapter Venetian Trading Firm of the Soranzo Brothers (1406-1434) and Its Commercial Network - Ryabova, Maria (Atti delle «Settimane di Studi» e altri Convegni, 2019)
This paper contributes to the discussion of merchant networks in late medieval Europe by presenting a case study of the Soranzo fraterna, a Venetian trading firm which comprised brothers Donado, Giacomo (Jacopo), Piero, and Lorenzo Soranzo and operated in the first half of the 15th century, specializing mainly in the import of raw cotton from Syria. The author applies the methodology of so-cial network analysis (SNA) in order to reconstruct the egocentric (ego-centered) network of ties linking the Soranzo firm ("the ego") with its partners and clients ("alters").